The Interrelationship of Adenomatoid Odontogenic Tumour and Dentigerous Cyst: A Report of a Rare Case and Review of the Literature. (12th December 2012) - Agarwal, Anshita; Giri, K. Y.; Alam, Sarwar
Abstract : The adenomatoid odontogenic tumor (AOT) is a relatively uncommon lesion which mainly affects females in their second decade of life, exhibiting predilection for the anterior region of the maxilla. The lesion is usually associated with the crown of an enclosed tooth, most commonly the maxillary canine. In this paper we present a case of adenomatoid odontogenic tumor associated with a dentigerous cyst affecting the left maxilla in a 15-year-old female. We also discuss clinical, radiographic, histopathologic, and therapeutic features of the case.